2014
DOI: 10.1210/jc.2013-2394
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk in Adult Patients With Growth Hormone (GH) Deficiency and Following Substitution With GH—An Update

Abstract: The GHD population may be considered at high cardiovascular risk, and GH substitution may be expected to bring an added value to patients with hypopituitarism in terms of cardiovascular protection. However, there is too limited evidence (rarely coming from randomized and controlled studies) to recommend GH treatment based on the cardiovascular status of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
82
2
20

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 144 publications
3
82
2
20
Order By: Relevance
“…AGHD often have significant changes in their lipid profile with increased LDL, increased 564 triglycerides, decreased high-density lipoprotein (HDL) (the latter observed only in women), with no 565 differences in lipoprotein (a) [139]. GH replacement positively reverses this negative lipid profile in…”
mentioning
confidence: 99%
“…AGHD often have significant changes in their lipid profile with increased LDL, increased 564 triglycerides, decreased high-density lipoprotein (HDL) (the latter observed only in women), with no 565 differences in lipoprotein (a) [139]. GH replacement positively reverses this negative lipid profile in…”
mentioning
confidence: 99%
“…A Dutch cohort of healthy subjects of resembling age demonstrated a higher increase in diastolic blood pressure during 6 years of follow-up (0.8 mmHg/year) (26). To date, only three studies have reported on the risk or incidence of CVDs in GH-treated adult patients with more than 2 years of follow-up (9,10,11,30). The assumed increased risk for CVDs diminished and even a decreased risk for CVDs was found in one (11).…”
Section: Discussionmentioning
confidence: 99%
“…During follow-up, despite an increase in waist circumference (especially in previous NFPA), the positive effect of GH treatment on lipid profile was evident in both groups. These positive effects of long-term GH treatment in all GHD patients on lipid profile have been demonstrated before, except for triglycerides for which results remain inconclusive (34,35), also in patients with GHD after acromegaly positive effects have been reported (17,20,28). However, most studies do not or are unable to take into account the use of lipid-lowering medication.…”
Section: European Journal Of Endocrinologymentioning
confidence: 91%